HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT YANG DIPERSEPSIKAN KELUARGA DENGAN TINGKAT KEPUASAN DI RUANG DAHLIA ATAS RSU KABUPATEN TANGERANG - Dwi Setyawati; M. Martono Diel; Neneng Gantini (Yayasan Nusantara Hasana Berdikari, 2024)
Communication is the first step in the nurse-patient relationship. The focus of communication is the patient's needs. Nurses must consider several factors in patients including physical condition, emotional state, cultural background, readiness to communicate and way of relating to others. Choosing when to communicate is also important when working with patients. Objective of this research to determine the relationship between therapeutic communication and the level of satisfaction in the Dahlia room at RSU Tangerang Regency. This research uses descriptive quantitative with a sampling technique, namely Total Sampling, totaling 16 respondents. Based on the analysis results of the chi-square statistical test, it was found that p-value = 0.003 so that the P value <0.05, which means Ho is rejected. So it can be concluded that there is a significant relationship between the therapeutic communication relationship and the level of satisfaction. There is a significant relationship between the nurse's therapeutic communication perceived by the family and the level of satisfaction in the upper dahlia room at RSU Tangerang Regency.